COVID-19 Pathophysiology Predicts That Ischemic Stroke Occurrence Is an Expectation, Not an Exception—A Systematic Review - Wijeratne, Tissa; Gillard Crewther, Sheila; Sales, Carmela; Karimi, Leila (Frontiers in Neurology, 2021)
Clinical reports of neurological manifestations associated with severe coronavirus disease 2019 (COVID-19), such as acute ischemic stroke (AIS), encephalopathy, seizures, headaches, acute necrotizing encephalitis, cerebral microbleeds, posterior reversible leukoencephalopathy syndrome, hemophagocytic lymphohistiocytosis, peripheral neuropathy, cranial nerve palsies, transverse myelitis, and demyelinating disorders, are increasing rapidly. However, there are comparatively few studies investigating the potential impact of immunological responses secondary to hypoxia, oxidative stress, and excessive platelet-induced aggregation on the brain. This scoping review has focused on the pathophysiological mechanisms associated with peripheral and consequential neural (central) inflammation leading to COVID-19-related ischemic strokes. It also highlights the common biological processes shared between AIS and COVID-19 infection and the importance of the recognition that severe respiratory dysfunction and neurological impairments associated with COVID and chronic inflammation [post-COVID-19 neurological syndrome (PCNS)] may significantly impact recovery and ability to benefit from neurorehabilitation. This study provides a comprehensive review of the pathobiology of COVID-19 and ischemic stroke. It also affirms that the immunological contribution to the pathophysiology of COVID-19 is predictive of the neurological sequelae particularly ischemic stroke, which makes it the expectation rather than the exception. This work is of fundamental significance to the neurorehabilitation community given the increasing number of COVID-related ischemic strokes, the current limited knowledge regarding the risk of reinfection, and recent reports of a PCNS. It further highlights the need for global collaboration and research into new pathobiology-based neurorehabilitation treatment strategies and more integrated evidence-based care.